Notes on Urban Mobility in Deindustrialized Cities: The Case of Greater ABC Region - Sampaio, Vitória Alves; Sígolo , Letícia Moreira (Electronic Journal "Fórum Ambiental da Alta Paulista", 2024)
The ABC Paulista, located in the São Paulo Metropolitan Area, was the birthplace of Brazilian Fordist peripheral industrialization, established its economic foundations in the automotive, chemical, metallurgical, and construction sectors. This industrial dynamism facilitated rapid urbanization during the 1950s, 1960s, and 1970s, resulting in a region characterized by disparities in housing conditions, access to infrastructure, urban services, employment opportunities, healthcare, education, culture, and leisure. Since the 1980s, the region has been experiencing the impacts of the process of productive restructuring, in conjunction with the ongoing industrial deconcentration across the country. This study aims to analyze these impacts in this peripheral region, considering changes in territorial organization and, particularly, in the mobility of people and goods, with a focus on urban mobility policies that have been planned and implemented. A literature review was carried out concerning the following subtopics: productive restructuring, industrial deconcentration, and deindustrialization; mainly focusing in alterations in the structural organization of the territory and their effects on mobility conditions in the Greater ABC Region; the characteristics of mobility and commuting patterns in the region; and the consequences of the national urban mobility policy in the Greater ABC Region. The results revealed that in recent years, the region has undergone transformations in its territorial organization that have implications for its mobility conditions, including an increase in intra and inter-regional commuting. Even though the development of regional and local policies aimed at addressing these challenges, such as regional and municipal urban mobility plans, more actions are necessary for constructing a path toward sustainable development as advocated by the Agenda 2030.